Pengaruh intervensi buah jambu biji terhadap kadar profil lipid pada orang dewasa dislipidemia - Asmarani, Asmarani; Purba, Martalena; Kandarina, Istiti (Jurnal Gizi Klinik Indonesia, 2019)
Background: Disease patterns originally dominated by infectious diseases and infections now change to those of degenerative disease, such as dyslipidemia, one of the risk factors forcoronary heart disease. In addition, excessive and unhealthy diet  gives  an effect on the lipidprofile. Fruits containing soluble fiber (pectin) and high vitamin C such as guavacan be use material for hypercolesterol amicin tervention. On the other hand,mild-moderate exercisealso hasa clear influenceon thedecrease of blood lipid profile.Objective: The aim of this research is to know the influence of guava (Psidium guajava) and sportson the lipid profileindyslipidemia in Kendari.Method: Type of of the research was quasi experimental design. Intervention group were given guava juice and exercise and exercise was only given in control groups. Subjects consume guava juice at a dose of 400 mg once daily with a volume of 250 ml each administration, performed for 30 days. Before interventions, blood samples for lipid profile have analyzed. The number of subjects for each group is 33 people (1:1). The data taken in the study are observations of the amountof blood lipid levels(mg/dl) such as high-densitylipoprotein (HDL), low density lipoprotein (LDL), triglycerides (TG) and total cholesterol (TC) using a standard method. Then, data were analyzed by using tests ofi Chi Square correlation and Wilcoxon Matched-pairs Signed-rank Test.Results: After 4 weeks oftreatment, the intervention significantly increased the levels of LDL 1 times higher (p<0.05) in the intervention group than that in the control group. The decrease of HDL in the intervention group was higher  than that  in the control group but it is not significantly different. In triglycerides and total cholesterol, the level decreased significantly higher in the intervention group compared to that of the control group (p <0.05)Conclusion: The guava juice is proven to be able to decrease LDL, triglycerides, total cholesterol, and LDL andincrease HDL levels.